Determining the Priority of the LKS-PWU Cash Waqf Aspect in Indonesia - Abimanyu, Agisni; Muslim; Ali, Mahbubi (SMART Insight, 2024)
Cash waqf is one of the instruments of Islamic philanthropy that has great potential in supporting sustainable social and economic development in Indonesia. In the context of its management, Sharia Financial Institutions Recipients of cash Waqf (LKS-PWU) play a strategic role as an intermediary between waqif and mauquf 'alaih. However, the effectiveness of cash waqf management is largely determined by various institutional, managerial, regulatory, and operational aspects that do not yet fully have clear priorities. This study aims to identify the priority of important aspects in the management of LKS-PWU cash waqf in Indonesia based on the consensus of experts. The method used is the Delphi method involving 11 experts consisting of academics, practitioners, and regulators of waqf. The results of the study show that of the 23 aspects of LKS-PWU cash waqf analyzed, as many as 19 aspects have reached a consensus, while the other 4 aspects have not been agreed. The three aspects with the highest priority are management professionalism, management productivity, and community education. These findings affirm the importance of strengthening managerial capacity and the quality of cash waqf management as the main prerequisites in improving the performance and sustainability of cash waqf in Indonesia.